Service Learning - Elrod, Leslie; Simon, Marilyn (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
According to the Center for the Enhancement of Teaching and Learning (n.d.) the benefits of service learning extend to students, faculty and the community.